Conceptual basis of international jurisdiction - N. Yu. Rubanenko (Bulletin of Kharkiv National University of Internal Affairs)
Constant changes in international relations and global challenges in the geopolitical arena disrupt the effectiveness and relevance of existing approaches to international justice. In this context, there is a need to analyze the conceptual foundations of this field in order to adapt to modern realities. The main goal of this study is to analyze the conceptual foundations of international justice, taking into account the latest scientific achievements and global perspectives. The focus of the research is the formation of new theoretical approaches and conceptual frameworks for the analysis and understanding of international criminal law. The methodological basis of the study is based on the analysis of scientific works in the field of international criminal law, as well as the use of modern scientific approaches to information processing. The article reveals new aspects and perspectives of the study of the conceptual foundations of international justice, which can contribute to the further development of the theory and practice of disclosure and investigation of serious violations of international law. The author highlights four conceptual ideas that underlie International Criminal Justice. The first concept concerns the principle of legality, which takes into account not only legal norms, but also social and legal transformations. The second idea considers the principle of international crime, which covers serious violations of international law. The third concept concerns individual responsibility for international crimes, regardless of the social status and official position of the subject of the offense. The fourth idea is the principle of universal jurisdiction, which provides a legal response to serious violations of international law, regardless of the circumstances and the subject of their commission. These concepts reflect the goal of international criminal justice, which is the inevitability of punishment for serious violations of international law, since their commission threatens the security of all humanity.